Phytochemical Investigation of Alkaloids from the Leaves of Elaeocarpus tectorius (Lour.) Poir. and Elaeocarpus angustifolius Blume - Ezeoke, Margret Chinonso (2019)
The genus Elaeocarpus (Elaeocarpaceae) has been reported as a producer of interesting indolizidine alkaloids. The leaves of Elaeocarpus tectorius (Lour.) Poir and Elaeocarpus angustifolius Blume were not previously phytochemically investigated. Preliminary test for presence of alkaloids on the leaf samples of both plants collected in Malaysia yielded positive results. The present study was therefore aimed at isolation and identification of new and bioactive compounds from the leaves of both plant species. A total of 16 alkaloids were identified in the present study. The leaves of E. tectorius yielded four new phenethylamine-containing alkaloids, namely, tectoricine (1), tectoraline (2), tectoramidine A (3) and tectoramidine B (4). These compounds represent the first occurrence of phenylethylamine-containing alkaloids from Elaeocarpaceae. Tectoricine (1) represents a novel isoquinuclidinone incorporating a phenethylamine moiety, while tectoraline (2) represents a rare alkamide incorporating two phenethylamine moieties. Tectoramidines A and B (3 and 4) represent the first naturally occurring trimeric and dimeric phenethylamine alkaloids incorporating an amidine function. The leaves of E. angustifolius yielded a total of 12 alkaloids, nine of which are new compounds. Seven of the nine new compounds obtained were indolizidine alkaloids, namely, carpusinine A (5), carpusinine B (6), carpusinine C (7a), epicarpusinine C (7b), carpusinine D (8), carpusinine E (9) and carpusidine (14), while the two remaining new compounds are pyrrolidine alkaloids, namely, carpusinine F (10a) and epicarpusinine F (10b). The three known alkaloids were identified as elaeokanine A (11), elaeokanine C (12) and elaeokanine D (13). The new carpusinine compounds (5 – 10) are alkylindolizidines that can be classified as elaeokanine-type alkaloids. Carpusidine (14) on the other hand represents the first simple indolizidine alkaloid isolated from Elaeocarpaceae. Compounds 5, 6, 7a/7b, 9, 11, 12, 13 and 14 were found to be non-cytotoxic when assessed using the CellTiter-Glo Luminescent Cell Viability Assay against a panel of 20 cancer cell lines and two normal human cell lines. In conclusion, chromatographic fractionation and purification of the alkaloid mixtures of the leaves of E. tectorius and E. augustifolous gave a total of 16 alkaloids including four phenylethylamine alkaloids, two pyrrolidine alkaloids and ten indolizidine alkaloids.